The Development of LKS Skill Oriented Sains Process In Optic Geometris Subject Using Guidance Inqury - Hamdanah, Siti; Arifuddin Jamal, Muhammad; Hartini, Sri (Universitas Lambung Mangkurat, 2017)
Students worksheet in the school during this time only contains description and questions. For this reason, the study is aimed to know about the worthiness of LKS Skill Oriented Sains Process on Subject Optic Geometries. The purpose of this study (1) to describe the validity of LKS based on test validity, (2) to describe the practical LKS which develop based on the learning implementation, (3) to describe the effectivity of LKS which developing based on studentsâ result of learning, scientific attitude, and Skill Oriented Sains Process. This research by using design of the study development, that is developing stage that adapted model Dick and Carey. The subject of this study is the researcher who has role as teacher and student is the eleventh grade students of Senior High School. The result of data analysis shows that the worthiness of LKS Skill Oriented Sains Process by using Learning Model Guidance Inquiry is the validity of LKS categorized as valid. The implementation of RPP is very good. The effectivity of LKS is effective. The conclusion is the development of LKS Skill Oriented Sains Process in Optic Geometries Subject Using Guidance Inquiry fulfill the criteria suitable to use.Â